Profile of Students' Errors in Mathematical Proof Process Viewed from Adversity Quotient (AQ) - Ekayanti, Arta; Nasyiithoh, Hikma Khilda (Universitas Islam Negeri Raden Intan Lampung, 2018)
Mathematical proof is an important aspect in mathematics, especially in analysis. An error in the mathematical proof construction process often occurs. This study aims to analyze the students’ errors in producing proof. Each of the categories of students’ Adversity Quotient (AQ) is identified related to the type of students’ error. The type of students’ errors used according to Newmann’s Error Analysis. This study used a qualitative approach. This study was conducted to 25 students who were taking real analysis course. Documentation, test, and interview were used to gather the data. Analyzing the students’ test result and then interviewing them for each AQ category were done for the analysis process. The results show that there are 48% climber students, 52% camper students, and no one is identified as a quitter student. Climber students tend to make some proving error such as transformation error, process skill error, and encoding error while camper students make the comprehension error, transformation error, process skill error, and encoding error when they are producing proof.